Pengaruh Literasi Keuangan, Locus of Control Dan Sikap Keuangan Terhadap Perilaku Konsumtif Mahasiswa - Miranda; Nurjanah; Ade Fadillah FW Pospos (Jurnal Investasi Islam, 2024)
This research aims to determine the influence of financial literacy, locus of control and financial attitudes on the consumptive behavior of FEBI IAIN Langsa students. This research uses quantitative methods. The sampling technique used was a simple random sampling technique using the Slovin formula so that 86 respondents were obtained. Data collection was carried out through observation and using questionnaires. The data obtained was tested for suitability using validity, reliability and classical assumption tests. Meanwhile, to test the hypothesis, multiple linear regression analysis tests are used which include the t test, F test and coefficient of determination test. The research results show that financial literacy has a positive and significant effect on students' consumptive behavior. Locus of control has a positive and significant effect on student consumer behavior. Financial attitudes have a positive and significant effect on students' consumptive behavior. Financial literacy, locus of control and financial attitudes have a positive and significant effect on students' consumptive behavior. From the results of this research, it is known that students can improve financial literacy, locus of control and good financial attitudes so that students are able to manage their finances efficiently so that students will be wiser in using their money and avoid consumptive behavior